A PORTRAIT OF STRATEGIES TO PROMOTE STRUGGLING READERS’ ENGAGEMENT IN JUNIOR HIGH SCHOOL - Sri Wahyuni; Aan Erlyana Fardhani; David Imamyartha (Wiralodra English Journal, 2024)
The present study sought to investigate the strategies employed by an English teacher in teaching reading at a junior high school. Different from previous research, which generally recruited several respondents, this study exclusively focused on a single teacher. This enabled a more detailed exploration of instructional strategies geared to a specific classroom setting. Employing qualitative descriptive design, the research was geared to examine the types of instructional strategies the teacher engaged, how these strategies were put at play, and their effectiveness in promoting students' English reading engagement. Data collection methods included observations and interviews with the teacher. The collected data were analyzed using qualitative analysis method. The findings unveiled that the teacher employed three main strategies for teaching reading: Question Answer Relationship Strategy, Reciprocal Teaching Strategy, and Imitation Strategy. These strategies were critical in enhancing students' comprehension of English texts through collaborative learning in making meaning based on provided texts. The findings underlined the importance of tailored instructional approaches that promote students’ active participation and reading engagement. This research contributes to the discussion on reading instruction by identifying practical strategies that can be adapted and implemented by English teachers to foster students' reading engagement effectively.